Pemetaan Titik Lokasi Infrastruktur di Desa Penda Pilang dengan Menggunakan GPS Map Garmin 64 SC, Kabupaten Gunung Mas, Provinsi Kalimantan Tengah - Noveriady Noveriady; Novalisae Novalisae; I Putu Putrawiyanta; Ferdinandus Ferdinandus; Neny Fidayanti (I-Com: Indonesian Community Journal, 2024)
Community Service Program (PKM) Mapping Infrastructure Location Points using satellite-based GPS in Penda Pilang Village in order to prepare location information and types of infrastructure facilities available, and can be used as a base map in future infrastructure development. The product resulting from this activity is a Map of Infrastructure Location Points in Penda Pilang Village, Kurun District, Gunung Mas Regency, Central Kalimantan Province. On the map, there are 9 (nine) physical infrastructures consisting of Village Gate, Church, Village Office and BPD, PAUD, Kindergarten, Elementary School, Middle School, Posyandu, and Community Health Center.